2016
DOI: 10.1136/jnnp-2016-313736
|View full text |Cite
|
Sign up to set email alerts
|

Peer support and reminiscence therapy for people with dementia and their family carers: a factorial pragmatic randomised trial

Abstract: ObjectiveThe objective of this study was to evaluate peer support and reminiscence therapy, separately and together, in comparison with usual care for people with dementia and their family carers.DesignFactorial pragmatic randomised trial, analysed by treatment allocated, was used for this study.SettingThe trial ran in Community settings in England.ParticipantsPeople with dementia and their family carers were the participants.InterventionsTreatment as usual (TAU) plus one of the following: one-to-one peer supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(116 citation statements)
references
References 26 publications
1
108
1
6
Order By: Relevance
“…In total 28 original studies were identified that tested an intervention comprising solely of peer support or had a peer support component. We examined the extent, nature and distribution of the studies included in this review and determined the following: the majority of studies ( n = 12) used a trial design including randomised controlled trials, pragmatic randomised trials, randomised controlled evaluations, randomised controlled two group design or randomised pilot studies (Charlesworth et al, ; Finkel et al, ; Gaugler et al, , , , ; Gaugler, Reese, Reese, & Mittelman, ; Hayden, Glynn, Hahn, Randall, & Randolph, ; Laakkonen et al, , ; Lai et al, ; Martindale‐Adams, Nichols, Burns, Graney, & Zuber, ; Mittelman et al, ; Núñez‐Naveira et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ; Winter & Gitlin, ), eight studies used a pre/post‐test design (Boots, de Vugt, Withagen, Kempen, & Verhey, ; Chenoweth et al, ; Chu et al, ; Dam, van Boxtel, Rozendaal, Verhey, & de Vugt, ; Gaugler, Hobday, et al, ; Hsu et al, ; Javadpour, Ahmadzadeh, & Bahredar, ; O'Connor, Arizmendi, & Kaszniak, ), four a quasi‐experimental design (Andren & Elmståhl, , ; Easom, Alston, & Coleman, ; Marziali & Garcia, ; Pagán‐Ortiz, Cortés, Rudloff, Weitzman, & Levkoff, ), two a quasi‐experiment with mixed methods design (Baily, Kingsyon, Alford, Taylor, & Tolhurst, ; Küçükgüçlü, Akpınar Söylemez, Yener, & Işık, ) and the final two studies used mixed methods (Hattink, Droes, Sikkes, Oostra, & Lemstra, ; McKechnie, Barker, & Stott, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total 28 original studies were identified that tested an intervention comprising solely of peer support or had a peer support component. We examined the extent, nature and distribution of the studies included in this review and determined the following: the majority of studies ( n = 12) used a trial design including randomised controlled trials, pragmatic randomised trials, randomised controlled evaluations, randomised controlled two group design or randomised pilot studies (Charlesworth et al, ; Finkel et al, ; Gaugler et al, , , , ; Gaugler, Reese, Reese, & Mittelman, ; Hayden, Glynn, Hahn, Randall, & Randolph, ; Laakkonen et al, , ; Lai et al, ; Martindale‐Adams, Nichols, Burns, Graney, & Zuber, ; Mittelman et al, ; Núñez‐Naveira et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ; Winter & Gitlin, ), eight studies used a pre/post‐test design (Boots, de Vugt, Withagen, Kempen, & Verhey, ; Chenoweth et al, ; Chu et al, ; Dam, van Boxtel, Rozendaal, Verhey, & de Vugt, ; Gaugler, Hobday, et al, ; Hsu et al, ; Javadpour, Ahmadzadeh, & Bahredar, ; O'Connor, Arizmendi, & Kaszniak, ), four a quasi‐experimental design (Andren & Elmståhl, , ; Easom, Alston, & Coleman, ; Marziali & Garcia, ; Pagán‐Ortiz, Cortés, Rudloff, Weitzman, & Levkoff, ), two a quasi‐experiment with mixed methods design (Baily, Kingsyon, Alford, Taylor, & Tolhurst, ; Küçükgüçlü, Akpınar Söylemez, Yener, & Işık, ) and the final two studies used mixed methods (Hattink, Droes, Sikkes, Oostra, & Lemstra, ; McKechnie, Barker, & Stott, ).…”
Section: Methodsmentioning
confidence: 99%
“…Inherent in this directive is the need to strengthen services that reflect the needs of the person with dementia and their informal carers. In response to these concerns a number of studies have suggested that psycho‐educational care interventions, containing facilitated peer support, could be of significant value to reduce psychosocial stress of being a carer (Charlesworth et al, ). Such support may be more effective when provided by a peer i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment, behavioural and psychological symptoms, depression y y n y n n (Continues) ADL/IADL functioning for up to 4 months, relative to control conditions. 50 45 Multicomponent interventions were diverse in both delivery and results, with 2 of 3 small studies demonstrating functional benefits.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 A reminiscence therapy study demonstrated no effects. 50 Cognitive training and stimulation therapies provided mixed results, with three out of six studies demonstrating evidence of efficacy of individual or group interventions (Tables 4, 5).…”
Section: Discussionmentioning
confidence: 99%
“…Patients are not the only beneficiaries of peer support, and nurses or other caregivers can benefit from it (Charlesworth et al, ; Taylor, Gutteridge, & Willis, ). At the end of the program, three nurses were asked what impact peer support had on them.…”
Section: Discussionmentioning
confidence: 99%